Integrated postural analysis in children with haemophilia. (March 2014) - Boccalandro, E.; Pasta, G.; Mannucci, P. M.; Santagostino, E.; Peyvandi, F.; Seuser, A.; Mancuso, M. E.; Solimeno, L. P.
Summary The maintenance of a correct posture in haemophilic boys might contribute to prevent joint bleeds, chronic pain and dysfunction. This single‐centre study was aimed at evaluating whether or not postural alterations are more common in haemophilic than in non‐haemophilic boys and whether they are related to the orthopaedic status. Posture and balance were investigated in boys with severe/moderate haemophilia (cases) and in age‐matched non‐haemophilic peers (controls). Thirty‐five cases (89% with haemophilia A: 74% with severe disease) were included in the study and compared with 57 controls. Posture was evaluated on digital pictures of anterior, lateral and posterior views of the habitual standing position. Balance was examined with a portable force platform with eyes open and closed. The trajectory of the total body centre of force (CoF) displacement over the platform was computed by multiple planes obtaining different measures: sway area, velocity, acceleration and body loads. The joint status of cases was assessed with the Haemophilia Joint Health Score. Cases were more disharmonic than controls (52% vs. 26% in controls; P = 0.04), swayed significantly less and more slowly than controls (P < 0.05 for several parameters of CoF displacement) revealing stiffness of the musculoskeletal system. However, they were able to maintain their stance within a similar sway area. Haemophilic boys have more postural disharmonies than non‐haemophilic peers, hence a global evaluation of the orthopaedic status should include also balance and posture examination to identify early dysfunction and establish a tailored physical or rehabilitation programme.